The role of urban renewal in creating authentic travel experience of urban tourism, a case study of Türkiye and Malaysia - Mohd Rozmadi, Nur Amalia Amani; Sahrul Anuar, Farah Aqillah; Rabe, Noor Suzilawati (IIUM Press, 2023)
This article discussed a findings from a comparative analysis on urban renewal initiatives and their impacts on the urban tourism landscape in the Malaysia and Türkiye. These countries boast a wealth of cultural heritage and historical significance, rendering the place as good case studies for investigating the profound consequences of urban renewal on the tourism industry. In this study, definition of urban renewal in the context of urban tourism, encompassing an intricate understanding of the strategies, challenges, and outcomes from the urban renewal programmes will be thoroughly discussed. Outcomes from this study are intended to provide valuable insights towards improving future urban development and tourism planning in both countries